APPLICATION OF NANOFLUIDS AS RADIATOR COOLANTS - A REVIEW - Rajkumar, Allociuos Britto; S, Bairavi; T, Banu; M.D, hreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
In general conventional fluids, such as water, engine oil and ethylene glycol are normally used as a heat transfer fluids. Nowadays the low performance of these conventional fluids obstructs the performance of radiators. The performance of an engine affects by various systems like fuel supply system, lubrication system, transmission system, cooling system etc. So, it becomes essential to account them while designing an engine for improves the engines performance. Cooling system is one of the important systems amongst all. It is responsible to carry large amount of heat waste to surroundings for efficient working of an engine.